Agroforestry suitability evaluation using remote sensing in Jatiyoso Sub-district, Karanganyar District, Central Java, Indonesia - SNADA INDAH TUK NEGARI; SESILIA RETNO AYU NINGTYAS; ZAHRA HANUN; MUHAMMAD NUR SULTON; LIA KUSUMANINGRUM; MUHAMMAD INDRAWAN; SUGIYARTO SUGIYARTO; SUTOMO SUTOMO; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Negari SIT, Ningtyas SRA, Hanun Z, Sulton MN, Kusumaningrum L, Indrawan M, Sugiyarto, Sutomo, Setyawan AD. 2023. Agroforestry suitability evaluation using remote sensing in Jatiyoso Sub-district, Karanganyar District, Central Java, Indonesia. Biodiversitas 24: 6761-6769. Agroforestry systems are critical for biodiversity conservation, land degradation mitigation, and climate change mitigation. This agroforestry approach reduces forest degradation, boosts food security, and gradually raises farmers' income. This study uses remote sensing and Geographic Information System (GIS) modeling tools to analyze land potential and agroforestry status in Jatiyoso Sub-district, Karanganyar District, Central Java, Indonesia. The data used in the analysis support data for soil fertility index, rainfall, Shuttle Radar Topography Mission (SRTM) satellite image data, and Normalized Difference Vegetation Index (NDVI). Modeling was done by integrating various thematic layers in the GIS domain. Weighting was also carried out in the analysis of land suitability. The mapping results in Jatiyoso Sub-district, Karanganyar District, showed that 18.1% (13.49 km2) had high potential as agroforestry areas, 54.9% (40.95 km2) had medium potential, and 27% (20.18 km2) had low potential. As a result, using remote sensing and GIS to determine suitable land for agroforestry could significantly impact the community, particularly farmers, landowners, and foresters, in the decision-making process for developing agroforestry systems and practices and estimating important productivity indicators. The most promising and appropriate agroforestry plants developed in Jatiyoso Sub-district are medicinal plants, but agricultural commodities like cloves, bananas, and vegetables are also present.